Efficacy and safety of Xiangsha liujunzi decoction for functional dyspepsia: a systematic review and meta-analysis - Wang, Longhua; Ding, Xia; Yao, Xinning; Li, Ping; Zhang, Fuwen; Wang, Fenglei; Li, Bai; Li, Jing (Frontiers in Pharmacology, 2024)
Background: Functional dyspepsia is a highly prevalent digestive disorder. The limited effectiveness of current pharmaceutical interventions necessitates the exploration of alternative therapeutic options for functional dyspepsia. Xiangsha liujunzi decoction, a well-known traditional Chinese medicine formulation, has been widely employed in the treatment of functional dyspepsia in China. Nevertheless, the effectiveness of Xiangsha liujunzi decoction in the treatment of functional dyspepsia remains uncertain.Objective: To examine the effectiveness and safety of Xiangsha liujunzi decoction for treating functional dyspepsia.We retrieved seven databases containing randomized controlled trials on functional dyspepsia published up until July 31, 2023. The quality of these studies was evaluated using the Cochrane Risk of Bias assessment tool. The analysis of data was performed using the software RevMan 5.4. The total clinical effectiveness rate was evaluated as the primary outcome. In addition, gastric emptying rate, symptom score and safety evaluation were evaluated as the secondary outcomes.The meta-analysis included 23 studies, involving 2,101 individuals.Xiangsha liujunzi decoction demonstrated a significantly higher clinical effectiveness rate compared to the control group (RR 1.27; 95% CI 1.21, 1.33; p＜0.00001).Moreover, it exhibited superior gastric emptying rate and symptom score improvement compared to the control group. Nevertheless, no remarkable differences were detected in safety between Xiangsha liujunzi decoction and the control group 2 / 29 (RR 0.67; 95% CI 0.16, 2.76; P=0.58).The findings of this study suggest that Xiangsha liujunzi decoction exhibits effectiveness and no significant adverse events observed. However, because of the low quality of the enrolled studies, more high-quality and strict design randomized controlled trials are required in the future.